2019
DOI: 10.31186/j.agroind.8.2.150-158
|View full text |Cite
|
Sign up to set email alerts
|

Subtitusion of Rpo to Seasoning Oil and Acceptability and Fortification Potency of Vitamin a Trough Chicken Noodle

Abstract: This study aims to obtain the amount of RPO, ?-carotene content, increase of vitamin A availability after red palm oil was added to the seasoning. This research uses Completely Randomized Design (RAL) with one factorial that is RPO concentration (0%, 25%, 50%, 75% and 100%). The results showed that the content of ?-carotene in RPO was 348,23 ppm or equivalent to 28,44 ?g RE per gram, mie ayam seasoning with RPO 100% addition was the most favored and accepted chicken noodle condiment by consumer as a whole, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
4
0
2
Order By: Relevance
“…Indicate that the higher the RPOO substitution, the lower the panelists' preference for the taste of grilled meatball sauce. This is in line with Agustina et al (2019) research. The 5% level ANOVA test results showed that the substitution of RPOO in grilled meatball sauce had a significant effect on the panelists' preference for taste.…”
Section: Tastesupporting
confidence: 92%
See 2 more Smart Citations
“…Indicate that the higher the RPOO substitution, the lower the panelists' preference for the taste of grilled meatball sauce. This is in line with Agustina et al (2019) research. The 5% level ANOVA test results showed that the substitution of RPOO in grilled meatball sauce had a significant effect on the panelists' preference for taste.…”
Section: Tastesupporting
confidence: 92%
“…The graph of the panelists' preference for the color of the grilled meatball sauce can be seen in Figure 2. The results obtained in this study are in line with research by Agustina et al (2019), where the effects of organoleptic tests on color showed that the color of the chicken noodle seasoning with the highest color preference value was in the 25% RPOO substitution treatment with a value of 4.48 (like). However, Budiyanto et al ( 2019) reported that the color preference of siomay sauce increase with increasing concentration of RPOO in the sauce.…”
Section: Colorsupporting
confidence: 90%
See 1 more Smart Citation
“…Contoh pemanfaatan RPO fraksi olein yaitu pada substitusi minyak rendang lokan, dan minyak bumbu mie ayam. RPOO yang disubstitusi pada beberapa produk pangan tersebut menunjukkan peningkatan kandungan karoten, serta vitamin A yang berperan sebagai antioksidan (Agustina et al, 2019;Budiyanto et al, 2019;Budiyanto et al, 2023). Selain diolah menjadi RPO, minyak sawit juga berperan sebagai minyak sayur (medium dalam penggorengan), shortening dalam pembuatan roti, pengganti lemak hewan, lemak dalam manisan (produk confectionery), keju analog, dan lainnya (Sulaiman et al, 2022).…”
Section: Pendahuluanunclassified
“…Pemanfaatan kandungan karotenoid minyak sawit sebagai sumber provitamin A alami, baik yang diaplikasikan sebagai fortifikan bahan pangan maupun sebagai suplemen kesehatan, mulai diteliti oleh peneliti Indonesia pada beberapa tahun terakhir (Agustina, et al, 2018). Produksi minyak sawit yang melimpah di Indonesia dengan efektivitas provitamin A-nya menjadikan pemanfaatan RPO sangat potensial untuk dikembangkan.…”
Section: Pendahuluanunclassified